APPLICATION OF THE CALLA MODEL IN LISTENING LEARNING USING LEGENDARY STORY TEXT IN AN INTERESTING WAY - Padilah, Devi Hayati; Ramadani, Hera; Jubaedah, Indah; Yuningsih, Widia (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2025)
This study aims to analyze the use of the Cognitive Academic Language Learning Approach (CALLA) model in learning to listen to legendary story texts in early level students in the Indonesian Language Education Study Program, Siliwangi University. The CALLA model was chosen because it combines cognitive, metacognitive, and social-affective learning strategies that are believed to improve students' academic abilities and language skills. This study uses a descriptive method with a quantitative approach to assess the effectiveness of the application of the model in the context of listening learning. Data were obtained through the assessment of student learning outcomes after participating in CALLA-based learning. The results of the analysis showed that 46.15% of students scored in the good category, 35.90% were sufficient, 15.38% were very good, and 2.56% were less. This finding shows that most students have shown sufficient to good listening skills, although there are still a small number who need improvement. Thus, the CALLA model has proven effective in supporting the listening learning process, especially in improving understanding of narrative texts such as legendary stories. This study recommends wider application of the CALLA model as a new listening learning strategy and aims to develop students' academic language skills.